Soil erosion prediction using Morgan-Morgan-Finney model in a GIS environment in Northern Ethiopia catchment - Tesfahunegn, Gebreyesus Brhane; Tamene, Lulseged D.; Vlek, Paul L.G. (Hindawi Limited, 2014)
Even though scientific information on spatial distribution of hydrophysical parameters is critical for understanding erosion processes and designing suitable technologies, little is known in Geographical Information System (GIS) application in developing spatial hydrophysical data inputs and their application in Morgan-Morgan-Finney (MMF) erosion model. This study was aimed to derive spatial distribution of hydrophysical parameters and apply them in the Morgan-Morgan-Finney (MMF) model for estimating soil erosion in the Mai-Negus catchment, northern Ethiopia. Major data input for the model include climate, topography, land use, and soil data. This study demonstrated using MMF model that the rate of soil detachment varied from <20 t ha−1y−1to >170 t ha−1y−1, whereas the soil transport capacity of overland flow (TC) ranged from 5 t ha−1y−1to >42 t ha−1y−1. The average soil loss estimated by TC using MMF model at catchment level was 26 t ha−1y−1. In most parts of the catchment (>80%), the model predicted soil loss rates higher than the maximum tolerable rate (18 t ha−1y−1) estimated for Ethiopia. Hence, introducing appropriate interventions based on the erosion severity predicted by MMF model in the catchment is crucial for sustainable natural resources management.